PENGARUH MODAL KERJA TERHADAP PROFITABILITAS (STUDI KASUS PADA INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2009 – 2013) - Sari, Rahma Dian; Farida, Lena (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study aims to determine the effect of the level of working capital turnover on profitability in food and beverage industry companies listed in Indonesia Stock Exchange (BEI) in the period 2009 - 2013. The independent variables it is working capital turnover while its dependent variable is profitability, measured by using Return on Assets ratio (ROA), Return On Investment (ROI) and Return on Equity (ROE).The sample in this study were selected with certain criteria with menngunakan method sampling.Diperoleh purposive sample of five companies with the financial statements of the period 2009 – 2013 that was obtained by 25 observations.The results showed that the results of hypothesis testing t test, the result is a working capital does not significantly affect the Return On Assets (ROA), Return On Investment (ROI) and Return on Equity (ROE).Keywords: Working Capital, Return On Assets (ROA), Return On Investment (ROI) and Return on Equity (ROE).